2010
DOI: 10.1210/jc.2010-0720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parathyroid Hormone Treatment on Circulating Sclerostin Levels in Postmenopausal Women

Abstract: Circulating sclerostin levels correlate with bone marrow plasma levels and are reduced by intermittent PTH therapy in postmenopausal women. Further studies are needed to assess the extent to which decreases in sclerostin production contribute to the anabolic skeletal response to PTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
118
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(136 citation statements)
references
References 31 publications
12
118
2
3
Order By: Relevance
“…Of note, a similar inverse relationship between serum sclerostin and iPTH was recently reported in patients with primary hyperparathyroidism (24). As to circulating bone turnover markers, no correlation with serum sclerostin was found in patients with primary hyperparathyroidism (24) or in healthy postmenopausal women (25,26). However, the percentage changes in bone formation or resorption markers in early response to estrogen treatment in postmenopausal women Bone formation by osteoblasts is inhibited by SOST/sclerostin, which is expressed in osteocytes.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Of note, a similar inverse relationship between serum sclerostin and iPTH was recently reported in patients with primary hyperparathyroidism (24). As to circulating bone turnover markers, no correlation with serum sclerostin was found in patients with primary hyperparathyroidism (24) or in healthy postmenopausal women (25,26). However, the percentage changes in bone formation or resorption markers in early response to estrogen treatment in postmenopausal women Bone formation by osteoblasts is inhibited by SOST/sclerostin, which is expressed in osteocytes.…”
supporting
confidence: 65%
“…Of note, serum values of sclerostin were considerably higher in patients with stage 5D CKD (18) than in healthy control subjects, patients with primary hyperparathyroidism, or postmenopausal women without known CKD (23)(24)(25)(26). As suggested by Cejka et al (18), the difference between the population with CKD and people free of CKD may come from increased sclerostin retention secondary to renal function impairment and/or increased sclerostin production.…”
mentioning
confidence: 93%
“…It is important to characterize this abnormality because patients with CKD may be prone to early adynamic bone disease, which may further induce secondary hyperparathyroidism (13). Although sclerostin is influenced by age and other bone metabolic factors, such as parathyroid hormone, 25-OH vitamin D, and sex steroids (12,(14)(15)(16)(17), we found by multiple regression that GFR, sex, and serum phosphorus were the only measures associated with sclerostin concentration in patients with CKD.…”
Section: Discussionmentioning
confidence: 77%
“…The similarity of the response to that observed in MLO-Y4 cells is also consistent with this effect of SCL being on osteocytes. We previously showed that human osteocytelike cells were sensitive to the anti-anabolic effects of SCL at concentrations as low as 1 ng/ml, concentrations that are higher than but near to the levels reported in human serum of between 0.3 and 0.6 ng/ml [49,50,51]. This suggested that cells at the preosteocyte and osteocyte stages are major physiological targets for SCL [36].…”
Section: Discussionmentioning
confidence: 92%